2013
DOI: 10.4161/onci.23618
|View full text |Cite
|
Sign up to set email alerts
|

The microenvironment of human neuroblastoma supports the activation of tumor-associated T lymphocytes

Abstract: Tumor infiltration by lymphocytes has been linked to improved clinical outcome in children with neuroblastoma (NB) but T-cell activation has never been demonstrated to occur within the NB microenvironment. Here we show that tumor-associated lymphocytes (TALs) obtained from lesions representing all genetic subsets of NB and autologous peripheral blood lymphocytes (PBLs) analyzed on the day of tumor excision differed in composition, phenotype and functional characteristics. The NB microenvironment appeared to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 40 publications
1
43
1
Order By: Relevance
“…13 This has motivated recent efforts to identify agents and therapeutic strategies that can convert immunosuppressive NB tumors to a more immunogenic and T cell-inflamed ('hot') phenotype, which is associated with favorable outcome in NB. [14][15][16] The stimulator of interferon genes (STING) pathway has recently been identified as an important mechanism by which the innate immune system is capable of sensing tumors, in order to initiate a type I interferon (IFN-I)driven inflammatory program that stimulates dendritic cell (DC) cross-presentation of tumor antigens, ultimately leading to mobilization of tumor-specific CD8 + T cells. [17][18][19] Owing to this critical role in cancer immune surveillance, cyclic dinucleotide (CDN) STING agonists have emerged as a promising new class of therapeutics that activate innate immunity to increase tumor immunogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…13 This has motivated recent efforts to identify agents and therapeutic strategies that can convert immunosuppressive NB tumors to a more immunogenic and T cell-inflamed ('hot') phenotype, which is associated with favorable outcome in NB. [14][15][16] The stimulator of interferon genes (STING) pathway has recently been identified as an important mechanism by which the innate immune system is capable of sensing tumors, in order to initiate a type I interferon (IFN-I)driven inflammatory program that stimulates dendritic cell (DC) cross-presentation of tumor antigens, ultimately leading to mobilization of tumor-specific CD8 + T cells. [17][18][19] Owing to this critical role in cancer immune surveillance, cyclic dinucleotide (CDN) STING agonists have emerged as a promising new class of therapeutics that activate innate immunity to increase tumor immunogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…15 Despite the fact that density of T cells has been associated with favorable clinical outcome in neuroblastoma more than 40 years ago, 16,17 the current knowledge of the types of immune cells infiltrating neuroblastoma is limited to a few studies conducted on a small number of specimens. 18,19 Some authors identified populations of CD4 C and CD8 C T cells with an activated (CD25 C and/or HLA-DR C ) phenotype, 18 while others found CD25 C T cells or cells with effector memory (CCR7 ¡ CD45RA ¡ ) phenotype. 19 However, a detailed description of the various T-cell subsets resident within a large collection of neuroblastoma specimens is not currently available.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Some authors identified populations of CD4 C and CD8 C T cells with an activated (CD25 C and/or HLA-DR C ) phenotype, 18 while others found CD25 C T cells or cells with effector memory (CCR7 ¡ CD45RA ¡ ) phenotype. 19 However, a detailed description of the various T-cell subsets resident within a large collection of neuroblastoma specimens is not currently available.…”
Section: Introductionmentioning
confidence: 99%
“…Along similar lines, tumor-infiltrating cells including macrophages, 160 , 161 myeloid-derived suppressor cells, 162 - 164 and mesenchymal stem cells (MSCs) have been harnessed as vehicles to selectively deliver oncolytic viruses to neoplastic lesions while shielding them from neutralizing antibodies and protecting them from sequestration by the MPS 163 , 165 - 170 . Finally, several laboratories worldwide have demonstrated that the therapeutic profile of oncolytic virotherapy can be remarkably boosted by the co-administration of several chemotherapeutics, including (but not limited to) gemcitabine (an immunostimulatory nucleoside analog), 171 - 173 paclitaxel (a microtubular inhibitor), 174 - 176 temozolomide and cyclophosphamide (two alkylating agents), 72 , 177 - 179 sunitinib (a relatively unspecific tyrosine kinase inhibitor), 180 - 182 cisplatin (a non-immunogenic DNA-damaging agent), 183 - 186 various histone deacetylase inhibitors, 187 and 13- cis retinoic acid (a retinoid employed for the treatment of high risk neuroblastoma) 188 , 189 . Taken together, these findings indicate that oncolytic viruses can mediate therapeutically relevant anticancer effects in vivo.…”
Section: Introductionmentioning
confidence: 99%